Strange cocktail: translation and the making of modern Hebrew poetry - Jacobs, Adriana Ximena (Michigan studies in comparative Jewish cultures, 2018)
Where you take words -- Introduction: poetics and practices of translation in modern Hebrew poetry -- Voices near and far: historical perspectives on Hebrew poetry and (its) translation -- The go-betweens -- Paris or Jerusalem? Esther Raab, Baudelaire and the writing of Kimshonim -- Twice planted: Leah Goldberg's poetics of translation -- The missing element: prosthetic translation in thirty pages of Avot Yeshurun -- Like a centipede, multiple voices: Harold Schimmel and the poetry of translation -- Afterword: every poem a translation